Pengaruh Iklim Organisasi Dan Kedewasaan Individu Pegawai Terhadap Kinerja Pegawai Pada Dinas Badan Pengelola Keuangan Dan Aset Daerah (Bpkad) Kabupaten Serang - Nafiuddin; Deviyantoro; Anizir Ali Murad (Jurnal Akuntansi Manajemen (JAKMEN), 2022)
Employee performance can be influenced by many factors including Organizational Climate and Maturity. The object of this research is the Serang Regency Regional Financial and Asset Management Agency. The purpose of this study was to determine the effect of Organizational Climate and Individual Maturity on Employee Performance of the Financial Management Agency and Regional Assets of Serang Regency. The sample of this research was 59 respondents who were distributed to employees of the Serang Regency Regional Financial and Asset Management Agency. The analytical method used is the quantitative method, the analysis used is the classical assumption test, multiple linear regression analysis, the coefficient of determination and hypothesis testing using SPSS v.24 for windows. Based on the results of the study it can be concluded that: 1) Organizational Climate has a significant effect on employee performance, 2) Individual Maturity has no significant effect on employee performance, and 3) Organizational Climate and Individual Maturity jointly (simultaneously) have a significant effect on performance employee. With a determination coefficient value of 0.261% and the remaining 73.9% is influenced by other factors that were not examined by researchers.